2020
DOI: 10.1002/pbc.28222
|View full text |Cite
|
Sign up to set email alerts
|

Initial in vivo testing of a multitarget kinase inhibitor, regorafenib, by the Pediatric Preclinical Testing Consortium

Abstract: Background: Regorafenib is a small molecule multikinase inhibitor that inhibits multiple kinases including BRAF, KIT, PDGFRB, RAF, RET, and VEGFR1-3. Procedures:The in vivo anticancer effects of regorafenib were assessed in a panel of six osteosarcoma models, three rhabdomyosarcoma models, and one Ewing sarcoma model. Results:Regorafenib induced modest inhibition of tumor growth in the models evaluated. Conclusion:The overall pattern of response to regorafenib appears similar to that of the kinase inhibitor so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A list of currently enrolling clinical trials that are specifically recruiting patients with relapsed RMS can be found in Table 1. Supporting published preclinical data in RMS models exists for some of these studies [61][62][63][64][65][66][67][68].…”
Section: Rms Patients (Nct02567435)mentioning
confidence: 73%
“…A list of currently enrolling clinical trials that are specifically recruiting patients with relapsed RMS can be found in Table 1. Supporting published preclinical data in RMS models exists for some of these studies [61][62][63][64][65][66][67][68].…”
Section: Rms Patients (Nct02567435)mentioning
confidence: 73%
“…It has also been theorized to inhibit the progression of OS by inhibiting AKT and ERK‐mediated signalling pathways. Its biochemical characteristics are similar to sorafenib, though its pharmacological effects are noticeably stronger 77,78 . Regorafenib has shown some significant results in clinical trials of OS.…”
Section: Anti‐angiogenic Targeted Drugs For Osmentioning
confidence: 99%
“…Its biochemical characteristics are similar to sorafenib, though its pharmacological effects are noticeably stronger. 77 , 78 Regorafenib has shown some significant results in clinical trials of OS. However, the anti‐angiogenesis mechanism in the disease has not yet been illustrated.…”
Section: Anti‐angiogenic Targeted Drugs For Osmentioning
confidence: 99%
“…MKIs simultaneously target several kinases (6). Preclinical results have indicated the potential efficacy of MKIs against osteosarcoma; however, there is presently no approved MKI for first-line treatment of osteosarcoma (7,8).…”
mentioning
confidence: 99%